MINAT BACA AL-QUR’AN PADA SISWA DI SMP NEGERI 3 AMPEK NAGARI KAB. AGAM - Nadira Fitri Ramadani; Zulfani Sesmiarni; Wedra Aprison; Iswantir (Universitas Pahlawan Tuanku Tambusai, 2022)
This study discusses the interest in reading the Al-Qur'an in students at SMP Negeri 3 Ampek Nagari Kab. Religion with the background of the problem there are still students whose interest in reading the Al-Qur'an is low, because students are less enthusiastic in reading the Al-Qur'an. So in this case, it is very necessary for the teacher's efforts to increase interest in reading the Al-Qur'an in students. The purpose of this study was to find out how the students' interest in reading the Al-Qur'an was in students, as well as what factors influenced the interest in reading the Al-Qur'an in students at SMP Negeri 3 Ampek Nagari. This type of research uses field research, through a descriptive qualitative approach that describes a phenomenon that occurs in the field. The location of this research is in SMP Negeri 3 Ampek Nagari Kab. Agam, with key informants namely students of class VIII.C and supporting informants namely Islamic Religious Education (PAI) teachers at SMP Negeri 3 Ampek Nagari. In collecting data, researchers used observation, interviews, and documentation techniques. Meanwhile, to analyze the data, researchers used data reduction, data display (data presentation), and data verification (drawing conclusions). Based on the results of the research that the author has done, it can be concluded that there are some students who have low interest in reading the Qur'an (less). So to increase students' interest in reading the Al-Qur'an, it takes the efforts of teachers and parents in providing motivation, so that students' interest in reading the Al-Qur'an increases and is supported by facilities and infrastructure at school. One of the efforts that PAI teachers have given at school is by asking students to read/memorize as many short verses as possible. For students who memorize a lot, they will be rewarded, this is an example of motivation that can increase students' enthusiasm (interest) in reading the Al-Qur'an. Keywords: Interest in Reading the Qur'an, PAI